(untitled) (Damascus University Journal of arts and humanities sciences, 2023)
Abstract Border crossing are the first outlet for any country, it is the country’s gateway to the outside world and gaining international legitimacy and legality, through research the Nassib crossing was studid where the crossing is considered to be a source of economic recovery for Syria, Jordan, Lebanon, and the Arabian Gulf, In addition; it has a social importance in transporting passengers and a political one which is manifested in the government’s imposition of its sovereignty over its lands Nassib crossing is on the southern side of Syria in Daraa governorate and on the northern side of Jordan in the Mafraq governorate. The deductive approach was followed in the preparation of the research, which corresponds, to the quantitative mathematical method, based on the analysis of tables and the drawing of appropriate graphs and maps. The research showed the economic fessibility on Syria, Jordan, and Lebanon in the first period of the study which is from 2011to 2015 that is the period of the Syrian crisis where the crossing was in the period of economic recovery, During the crisis until the closure of the crossing, the results showed a decline in transit movements exports and imports with a decrease in the degree of importance of exports and a profitable trade balance for Syria with Jordan and Lebanon. As for the second period of the study it is the period of the closing the crossing (from2015to2018),as it shows a significant decrease in transit movement exports and imports and an indicator of the importance of exports significantly with a losing trade balance for Syria with both Lebanon and Jordan. Meaning that a significant decline occurred in the quantity and value of trade exchange, where Syrian loses amounted to 5400US, dollars against a loss of 900million for Lebanon and 800million for Jordan, as a result of the conditions of the Syrian crisis and the closure of the crossing. The research recommended the necessity of reopening the crossing because of its importance to Syria, Lebanon and Jordan.